MEDIA DAN KRISIS POLITIK (Analisis Wacana Terhadap Pemberitaan KOMPAS mengenai Krisis Politik Thailand, Edisi Maret-Mei 2010) - Agus Triyono; Joni Rusdiana (Jurnal Ilmiah Komunikasi Makna, 2012)
This study aims to examine the preaching of KOMPAS will be Thailandâ€™s political crisis. Questions to be answered in this study is how KOMPAS preach political crisis in Thailand. For this purpose, the researchers used a method of discourse analysis. Researchers analyzed at the level of textual and contextual KOMPAS news articles about Thailandâ€™s political crisis of 2010 for the March-May 2010. The ï€ rst ï€ ndings are at the beginning of Thailandâ€™s political crisis took place, KOMPAS does not cover the event directly. News about the crisis KOMPAS is taken from the source media and foreign news agencies such as: Bangkok Post, Reuters, The Nation, BBC, AP, AFP and fro. Only when the escalation of the crisis began peaking KOMPAS send reporters to cover the event directly. When the crisis began to subside KOMPAS pull back and re-use media journalists and foreign news agencies as sources of news. Second, related to the role of the media, in the context of Thailandâ€™s political crisis was initially KOMPAS acts as a transmitter, reported the news in an objective, accurate, neutral, and balanced. Then when the crisis began to escalate, it looks KOMPAS started giving appraisals. Lastly, KOMPAS gradually began to show partiality to the protesters commonly referred to as the â€œRed Shirtâ€.